2019
DOI: 10.1590/fst.21917
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-characterization and optimization of macro and micro nutrients for exopolysaccharides and mycelia growth in pleurotus tuberregium (RUMPH, EX FR)

Abstract: Nevertheless, the potential of P. tuberregium to produce EPS and fungus biomass for food and medicinal uses is underexplored. On addition, few studies have been conducted to identify the best cultivation conditions and extensive nutrient

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Notably, obvious differences in the phosphorus and sodium contents were reported from these two studies. These discrepancies might be attributed to the differences in geographic location and culturing conditions of the mushrooms used in these two studies that would greatly affect its mineral content . Furthermore, the biologically active ingredients identified in PTR , such as polysaccharides, alkaloids, phenolic compounds, tannins, saponins, hypericum glycosides, and flavonoids, have also gained much attention recently…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Notably, obvious differences in the phosphorus and sodium contents were reported from these two studies. These discrepancies might be attributed to the differences in geographic location and culturing conditions of the mushrooms used in these two studies that would greatly affect its mineral content . Furthermore, the biologically active ingredients identified in PTR , such as polysaccharides, alkaloids, phenolic compounds, tannins, saponins, hypericum glycosides, and flavonoids, have also gained much attention recently…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Same have been applied in beans, cassava, mushroom for crop improvement (Moyib et al, 2015a;Moyib et al, 2015b;Moyib et al, 2019).…”
Section: Moyib Ok; Omotola Oe; Banjoko Oo Ezike Bumentioning
confidence: 99%
“…Recently, research has shown that succinoglycan in the form of oligosaccharides was incorporated into fermented soy and rice-based beverages, bringing food alternatives to groups of individuals who have dietary restrictions (Nascimento et al, 2022). Due to the potential applicability of exopolysaccharides (Moyib et al, 2019), especially succinoglycan, in recent years several renewable carbon sources have been investigated for the production of bacterial biopolymers, aiming to produce biomaterials with lower environmental impact, higher performance, better applicability and lower production cost (Andhare et al, 2017b;Moosavi-Nasab et al, 2012).…”
Section: Introductionmentioning
confidence: 99%